Running biomechanics before and after Pose® method gait retraining in distance runners - Wei, R. X.; Au, I. P. H.; Lau, F. O. Y.; Zhang, J. H.; Chan, Z. Y. S.; MacPhail, A. J. C.; Mangubat, A. L.; Pun, G.; Cheung, R. T. H. (Sports Biomechanics, 2021)
Pose® Method gait retraining has been claimed to modify running form and prevent injury. This study examined the running biomechanics before and after Pose® Method gait retraining. Fourteen runners underwent a 4-week Pose® Method gait retraining program delivered by a certified coach. Paired t-tests were employed to compare vertical average (VALR) and instantaneous loading rates (VILR), lower limb kinematics, footstrike angle and trunk flexion in the sagittal plane before and after the training. Kinetically, there were no significant differences in the VALR (p= 0.693) and VILR (p= 0.782) before and after the training. Kinematically, participants exhibited greater peak hip flexion (p= 0.008) and knee flexion (p= 0.003) during swing. Footstrikeangle also reduced significantly (p= 0.008), indicating a footstrike pattern switch from rearfoot strike to midfoot strike. There was no significant difference in the trunk flexion in the sagittal plane after training (p= 0.658). After a course of Pose® Method gait retraining, runners demonstrated a footstrike pattern switch and some kinematics changes at the hip and knee joint during swing. However, injury-related biomechanical markers (e.g., VALR and VILR) and the trunk kinematics remained similar after training. Runners may consider other gait retraining programs for impact loading reduction.